2017
DOI: 10.1007/s00421-017-3595-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of quadriceps surface electromyography measurements is improved by two vs. single site recordings

Abstract: PurposeThe reliability of surface electromyography (sEMG) is typically modest even with rigorous methods, and therefore further improvements in sEMG reliability are desirable. This study compared the between-session reliability (both within participant absolute reliability and between-participant relative reliability) of sEMG amplitude from single vs. average of two distinct recording sites, for individual muscle (IM) and whole quadriceps (WQ) measures during voluntary and evoked contractions.MethodsHealthy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
(42 reference statements)
4
27
0
Order By: Relevance
“…Data in this experiment indicated that peak muscle activation recorded with surface EMG exhibited no relationship with PPO and thus was not a meaningful determinant of PPO in elite cyclists. Therefore, it is possible that more accurate and sensitive measures of neuromuscular activation, perhaps including surface EMG from more muscles and multiple sites per muscle, as well as alternative normalization techniques, might reveal a greater role for activation in determining PPO. However, given that muscle morphology explained 87% of the variability in PPO, the unexplained variance was relatively small (13%) and the contribution of other independent factors, including neuromuscular activation, appears limited for this performance task.…”
Section: Discussionmentioning
confidence: 99%
“…Data in this experiment indicated that peak muscle activation recorded with surface EMG exhibited no relationship with PPO and thus was not a meaningful determinant of PPO in elite cyclists. Therefore, it is possible that more accurate and sensitive measures of neuromuscular activation, perhaps including surface EMG from more muscles and multiple sites per muscle, as well as alternative normalization techniques, might reveal a greater role for activation in determining PPO. However, given that muscle morphology explained 87% of the variability in PPO, the unexplained variance was relatively small (13%) and the contribution of other independent factors, including neuromuscular activation, appears limited for this performance task.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly pertinent during MVCs, when motor unit activity is underestimated by sEMG due to the increasing number of simultaneous overlapping positive and negative phases of action potentials resulting in increased variability (Farina et al, 2014) 3) Number of electrodes. This experiment used one electrode per muscle group and though they were averaged over both muscle groups over both legs, it has been suggested that increasing the number of sEMG electrodes over a muscle group might help improve reliability particularly during MVCs (Balshaw et al, 2017), but of course this becomes inherently less practical, more complex, more time consuming, and hence more difficult to deliver in applied situations Other investigators also attribute the high levels of variability to a various factors including: psychological/motivational factors (Ball and Scurr, 2010;Bamman et al, 1997;Heinonen et al, 1994;Yang and Winter, 1983), synergetic muscle contribution (Miaki et al, 1999) and fatigue onset (Heinonen et al, 1994;Yang and Winter, 1983).…”
Section: Reliability Of Reference Tasksmentioning
confidence: 99%
“…Therefore, whether increases in agonist neuromuscular activation underpin joint angle specific strength increases after short-term SCT remains unclear. These contrasting findings may be due to a lack of contemporary sEMG methods such as joint angle specific M-wave normalization (Lanza et al 2017), duplicate sensors on each superficial constituent muscle (Balshaw et al 2017), and duplicate measurement sessions at each timepoint (i.e. pre and post training) to enhance measurement reliability.…”
Section: Introductionmentioning
confidence: 99%